Biofilm carriers for anaerobic ammonium oxidation: Mechanisms, applications, and roles in mainstream systems. (June 2022) - Gao, Dawen; Li, Yuqi; Liang, Hong
Graphical abstract: Highlights: Carriers hold respective advantages at different phase of AnAOB biofilm formation. The application status of carriers in ANAMMOX process was thoroughly discussed. The carrier modification method is summarized and classified into three categories. Four desirable characteristic is need for carriers applied in mainstream ANAMMOX. The mainstream ANAMMOX system is suggested to be realize with novel carriers. Abstract: The anaerobic ammonium oxidation (ANAMMOX) process was proposed as the most promising nitrogen removal process. Biofilm carriers were demonstrated to effectively enhance the anaerobic ammonium oxidating bacteria (AnAOB) retention. This paper reviews the effect of carrier properties on the AnAOB biofilm development according to the biofilm development process and the application state-of-art of three major kinds of conventional carriers, organic-based, inorganic-based carriers, and gel carriers, from the view of system performance and functional microorganisms. The carrier modification methods and purpose are thoroughly summarized and classified into three categories corresponding to various carrier defects. Four important aspects of the desirable carrier for the mainstream ANAMMOX process were proposed, including providing spatial configuration, enhancing the biomass retention, reinforcing the activity, and improving the growth environment, which needs to combine the advantages of organic and inorganic materials. Eventually, the future application directions of novel carriers for the ANAMMOX-based process were also highlighted.